Corrosion Resistance, Surface Evaluation, and Geometric Design Comparison of Five Self-Expanding Nitinol Stents Used in Clinical Practice. (April 2014) - Morrison, Jasper W.; Pelletier, Matthew H.; Rives, Alain; Walsh, William R.; Yang, Jia-Lin; Varcoe, Ramon L.
Purpose: To investigate the corrosion resistance properties of 5 commercially available nitinol stents used to treat peripheral artery disease and compare their surface quality, elemental composition, and geometrical design. Methods: Samples of 5 different designs of nitinol peripheral stents [LifeStent (n=4), Philon (n=6), Epic (n=6), S.M.A.R.T. Control (n=7), and Complete SE (n=7)] were examined using stereomicroscopy, environmental scanning electron microscopy, and x-ray photoelectron spectroscopy. Corrosion resistance testing was performed in accordance with ASTM International Standard F2129-08. Results: Thirteen (43%) of 30 stents corroded during this experiment. Stent fracture was observed in 12 (92%) of these corroded stents. Mean breakdown potentials ranged from 517 to 835 mV (vs. Ag/AgCl) for the Philon, Complete SE, S.M.A.R.T. Control, Epic, and LifeStent models from lowest to highest. A statistically significant difference in breakdown potential was observed between the LifeStent vs. Philon stents (835 vs. 517 mV, p=0.01) and Epic vs. Philon stents (833 vs. 517 mV, p=0.03). Stents with lower breakdown potential and relative breakdown potentials were associated with a higher fracture frequency (Spearman correlation coefficient −0.44, p=0.015 and −0.869, p<0.01, respectively). Conclusion: In this in vitro study, corrosion led independently to stent fracture. There is a significant association between lower mean breakdown/relative breakdown potentials and stent fracture.